Cranial Ultrasound and Minor Motor Abnormalities at 2 Years in Extremely Low Gestational Age Infants. Issue 4 (May 2020) - DeMauro, Sara B.; Bann, Carla; Flibotte, John; Adams-Chapman, Ira; Hintz, Susan R.
ABSTRACT: Objectives: The objectives of this study are to determine whether abnormalities on neonatal cranial ultrasound (CUS) are associated with minor motor abnormalities at 2 years' corrected age (CA) and to assess functional outcomes and resource utilization among children with minor motor abnormalities. Methods: Infants born at <27 weeks in the National Institute of Child Health and Human Development Neonatal Research Network between January 1, 2010, and December 31, 2014, who underwent neuroimaging with CUS at both <28 days and ≥28 days and were evaluated at 18 to 26 months' CA, were included. Follow-up included Bayley-3, neuromotor examination, Gross Motor Function Classification System (GMFCS) level, and parent questionnaires about special services and resource needs. Children were classified by the most severe motor abnormality at 18 to 26 months' CA as follows: none, minor, or major motor function abnormality. Minor motor abnormalities were defined as any of the following: (1) Bayley-3 motor composite, fine motor score, or gross motor score 1 to 2 SDs below the test normative means; (2) mild abnormalities of axial or extremity motor skills on standardized neuromotor examination; or (3) GMFCS level 1. Results: A total of 809 (35%) of 2306 children had minor motor function abnormalities alone. This did not increase substantially with CUS findings (no intraventricular hemorrhage [IVH]: 37%, grade I IVH: 32%, grade II IVH: 38%, grade III/IV IVH: 30%, isolated ventriculomegaly: 33%, and cystic periventricular leukomalacia: 24%). The adjusted odds of minor axial and upper extremity function abnormalities and GMFCS level 1 were significantly higher in children with more severe CUS findings. Children with minor motor abnormalities had increased resource utilization and evidence of functional impairment compared with those without motor function abnormalities. Conclusion: Minor motor abnormalities at 2 years' CA are common and cannot be predicted by neonatal CUS abnormalities alone. Minor motor abnormalities are associated with higher resource utilization and evidence of functional impairment. These findings have important implications for early counseling and follow-up planning for extremely preterm infants. Abstract : This article has supplementary material on the web site: www.jdbp.org.